Fostering Students’ Religious Character through the Dhamysoga Character Camp Co-Curricular Program - Khoridatul Masruroh; Muhammad Sulistiono; Dian Mohammad Hakim (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
Religious character development has become an important concern in contemporary education, particularly in response to moral challenges and the need to strengthen students’ values beyond academic achievement. Schools are therefore required to implement innovative educational programs that facilitate the internalization of religious values through meaningful learning experiences. This study aims to analyze the implementation of the Dhamysoga Character Camp (DCC) co-curricular program and its role in fostering students’ religious character at State Senior High School 5 Malang. This research employed a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation, and analyzed using the Miles and Huberman interactive model. The findings reveal that DCC is implemented through systematic planning, active student involvement, community-based activities, religious practices, and reflective sessions. The program integrates experiential learning through three interconnected components: active student participation, social interaction and community service, and reflective processes. These components enable students to internalize religious values through direct experience, meaningful social engagement, and spiritual reflection. As a result, DCC contributes to the development of students’ religious character by fostering religious awareness, responsible behavior, empathy, and social responsibility in a conscious and sustainable manner. The study concludes that DCC represents an experiential learning-based model of religious character education that effectively integrates personal, social, and spiritual dimensions within a co-curricular setting.